Yield growth patterns of food commodities: Insights and challenges. - John Baffes; Xiaoli Etienne (PLoS ONE)
Understanding global food production and productivity patterns is crucial for policy and investment decisions aimed at addressing poverty, food insecurity, and climate change. This paper develops comprehensive calorific-based production and yield indices for 144 crops, covering 98% of global agricultural land and food output. These indices provide standardized measures across various crops and varieties, facilitating comparison of agricultural productivity and consolidating country and regional contributions to global food production. Utilizing a Box-Cox transformation, we find that a linear model best approximates yield growth. Our findings reveal that, at an aggregate level, there has been no discernable slowdown in global yield growth over the past six decades. This translates into an average annual yield increase equivalent to nearly 33 kilograms of wheat per hectare. These results suggest that any observed deceleration in specific commodities, regions, or countries, has been offset by gains in others. While these findings are reassuring from a global food supply perspective, caution is warranted about the sustainability of production and the affordability of food. These concerns are particularly relevant as global food demand increases due to population and income growth, and as the pressures from climate change intensify. The study underscores the importance of adopting strategic and sustainable agricultural practices to ensure continued food security in the face of evolving global challenges.